Upper Egyptian Vessels at Tell el-Ghaba, North Sinai: Luxury Objects of the Local Elite - Lupo, Silvia Alicia (2011)
Tell el-Ghaba is an archaeological site of the 26th Dynasty (late 7th to early 6th century BC) situated next to the Pelusiac branch of the Nile, which at that time was part of the Eastern Delta. The site was part of the expansionary policy towards the Levant adopted by the Saite kings at a period when the commercial exchange across the eastern Mediterranean was at its peak. The Argentine Archaeological Mission undertook research at Tell el-Ghaba as part of a salvage project under the auspices of UNESCO aimed at investigating the Northern Sinai site threatened by irrigation works at the region.1 Several buildings were found during the excavations in 1995–1999 and 2010. A geomagnetic survey carried out in 2010 by Tomasz Herbich2 allowed to determine the limits of the site; also, several buildings and structures were detected that confirmed the urban planning for the site.